2022
DOI: 10.1101/2022.05.03.490469
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantum CART(qCART), apiggyBac-basedsystem for development and production of virus-free multiplex CAR-T cell therapy

Abstract: Chimeric antigen receptor T (CAR-T) cell therapy has the potential to transform cancer treatment. However, CAR-T therapy application is currently limited to certain types of relapse and refractory liquid tumors. To unlock the full potential of CAR-T therapy, technologic breakthroughs will be needed in multiple areas, including optimization of autologous CAR-T development, shortening the innovation cycle, and further manufacturing advancement of next-generation CAR-T therapies. Here, we established a simple and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 62 publications
2
18
0
Order By: Relevance
“…Genotoxicity is also a predominant safety issue associated with gene therapy products. Consistent with our previous study, we observed low risk of genotoxicity in qCART TM -manufactured CAR-T cells, given the low integrant copy number, safe integration profile, low enhancer activity, and low residual Quantum pBase, suggesting minimal integrant remobilization risks 45 (Supplementary Figure 1B; Figure 2B). Furthermore, acute toxicities in patients in response to CAR-T therapies, such as CRS and ICANS, have been major concerns in CAR-T development.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Genotoxicity is also a predominant safety issue associated with gene therapy products. Consistent with our previous study, we observed low risk of genotoxicity in qCART TM -manufactured CAR-T cells, given the low integrant copy number, safe integration profile, low enhancer activity, and low residual Quantum pBase, suggesting minimal integrant remobilization risks 45 (Supplementary Figure 1B; Figure 2B). Furthermore, acute toxicities in patients in response to CAR-T therapies, such as CRS and ICANS, have been major concerns in CAR-T development.…”
Section: Discussionsupporting
confidence: 91%
“…4,19,20 While we also used aAPC in our initial experiments, we could generate sufficient quantity of patient-derived qCART™ -modified CAR-T cells without aAPC-induced enrichment. Our recent study further confirmed that qCART™ -manufactured CAR-T cells may be more effective in tumor control without aAPC enrichment 45 . Here, we demonstrated that 2.29×10 8 –1.38×10 9 T cells could be generated in a 1 L-G-Rex within a short time-frame of 12 days using T cells from patients with B-cell malignancies.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Given the low frequency of footprint-induced mutation by piggyBac (< 5 %) and the fact that only a minimal portion (< 0.4 %) of CAR + T cells expressed detectable level of qPBase in CAR-T cells (Figure 5B), transposase in a plasmid form should be sufficiently safe when applied to highly proliferative ex vivo -engineered cells. Additionally, our recent genome-wide integration profiling of qPB in CAR-T products derived from two distinct donors further support its safe use in T cell engineering(52).…”
Section: Discussionmentioning
confidence: 69%